Pengaruh Pembelajaran Accelerated Include Blended Learning Berbasis Penguatan Karakter Mahasiswa - Ika Nurani Dewi; Sumarjan Sumarjan; Sri Nopita Primawati (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2023)
The aim of the study was to determine the effect of the implementation of Accelerated Include Blended Learning based on character strengthening on the character of discipline, independence, and student responsibility. This type of research is a quantitative descriptive research using a survey approach. The research sample consisted of 74 students Department of Forestry in the first semester of the 2021/2022 academic year. Purposive random sampling was used as a sampling technique. The research instrument consisted of a character self-assessment questionnaire which before use was tested for the validity and reliability of Cronbach's Alpha. The data analysis technique uses the F test to determine the effect of Accelerated Include Blended Learning on the formation of student character. The results showed that: 1) Accelerated Include Blended Learning had an effect on students' independent character in class A and B with a significance value of p < 0.05; 2) Accelerated Include Blended Learning had an effect on the discipline character of students in class B with a significance value of p < 0.05, but has no effect on class A students with a significance value of 0.262 > 0.05; and 3) Accelerated Include Blended Learning influences the character of the responsibilities of class A and B students with a significance value of p < 0.05.